Impact of Changes in Accounting Standards in Debt Ratios of Firms: Evidence in Brazil - André Aroldo Freitas de Moura (FUCAPE Business School, 2016)
ABSTRACT This research investigates the impact of changes in debt ratios of Brazilian firms due to the IFRS adoption. We make a comparison between the forecast of the time-series of debt ratios accounted until 2007 for the span from 2008 to the first quarter of 2015 with those effectively accounted from 2008 to the first quarter of 2015 derived from the new accounting standard. The research utilizes SARIMAX model and Chow’s (1960) structural break forecast test, controlling for changes originating from the macroeconomic environment as well. We find evidence of significant changes in the debt ratio towards both higher and lower debt with predominance of greater ratios. This result is consistent with past literature in Europe, Australia and New Zealand. Nevertheless, we do not find evidence of a structural break in the Financial Dependency ratio. Moreover, there is no evidence of any distinct effects across different industries. The research provides new evidence confirming the informational effects of IFRS by utilizing a robust time-series model with macroeconomic controls in an innovative approach towards the accounting environment.